(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: One of the promising areas in ophthalmology is photodynamic therapy (PDT). Purpose: To assess the effect of laser irradiation of the rat eye at the doses applied in PDT (without photosensitizer) on endogenous intoxication indices. Materials and Methods: Fifty rats were used to investigate the effect of different modes of photodynamic irradiation of the rat eye on changes in endogenous intoxication indices over time. Results: Exposure to 630-nm laser irradiation of 300-mJ pulsed mode (3 min) and 60-J photodynamic dose (PDD) mode (15 s) does not result in the development of endogenous intoxication. According to the literature, serum level of middle-weight molecules (MWM) is an integral marker of metabolic disorders of the body and can be used as evidence of the intensity of endogenous intoxication. Conclusion: Exposure to 630-nm laser irradiation of 300-mJ pulsed mode (3 min) and 60-J PDD mode (15 s) does not result in the development of endogenous intoxication, making possible the application of these modes in practical ophthalmology. Because exposure to 890-nm laser irradiation of 300-mJ pulsed mode (3 min), and, especially, to 630-nm laser irradiation of 120-J PDD mode (30 s) results in the increased accumulation of MWM in circulating blood of animals, the eye should not be exposed to such irradiation doses.